2013
DOI: 10.1104/pp.113.220426
|View full text |Cite
|
Sign up to set email alerts
|

Mutually Exclusive Alterations in Secondary Metabolism Are Critical for the Uptake of Insoluble Iron Compounds by Arabidopsis and Medicago truncatula

Abstract: ORCID IDs: 0000-0002-7967-5136 (J.R.-C.); 0000-0001-5470-5901 (J.A.); 0000-0002-7850-6832 (W.S.).The generally low bioavailability of iron in aerobic soil systems forced plants to evolve sophisticated genetic strategies to improve the acquisition of iron from sparingly soluble and immobile iron pools. To distinguish between conserved and species-dependent components of such strategies, we analyzed iron deficiency-induced changes in the transcriptome of two model species, Arabidopsis (Arabidopsis thaliana) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
253
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(277 citation statements)
references
References 52 publications
16
253
0
2
Order By: Relevance
“…Rodríguez-Celma et al (2013) showed that secretion of phenolics is critical for Arabidopsis Fe acquisition from low bioavailability sources, and then Fourcroy et al (2014) and Schmidt et al (2014) demonstrated that coumarins are the active compounds in this process. Schmid et al (2014) confirmed that secretion of coumarins is an essential aspect of Arabidopsis Fe acquisition and provided extensive information on metabolomic changes elicited by Fe deficiency.…”
mentioning
confidence: 99%
“…Rodríguez-Celma et al (2013) showed that secretion of phenolics is critical for Arabidopsis Fe acquisition from low bioavailability sources, and then Fourcroy et al (2014) and Schmidt et al (2014) demonstrated that coumarins are the active compounds in this process. Schmid et al (2014) confirmed that secretion of coumarins is an essential aspect of Arabidopsis Fe acquisition and provided extensive information on metabolomic changes elicited by Fe deficiency.…”
mentioning
confidence: 99%
“…Recently, it has been shown that root exudates including phenolics and riboflavin derivatives function as iron-binding compounds in Arabidopsis and Medicago truncatula, similar to those in the chelation-based Strategy II response. The induction of phenylpropanoid and flavin pathway genes is tightly linked to core genes of the iron acquisition machinery, such as FIT, FRO2, IRT1, and AHA2, and thus appears to constitute an integral component of the Strategy I response in Arabidopsis and M. truncatula (Rodríguez-Celma et al, 2013).…”
mentioning
confidence: 99%
“…Both these genes are strongly up-regulated by iron deficiency, and regulatory proteins governing the expression of these genes have been the subject of intense investigation (Colangelo and Guerinot, 2004;Jakoby et al, 2004;Yuan et al, 2005Yuan et al, , 2008Bauer et al, 2007;Wang et al, 2007;Long et al, 2010;Selote et al, 2015;Li et al, 2016;Mai et al, 2016). An additional component of iron uptake in nongraminaceous plants is the discovery that iron deficiency induces the secretion of phenolics and flavins (Rodríguez-Celma et al, 2013), later better defined as coumarins (Schmid et al, 2014) that are secreted by the ABCG37/PDR9 transporter (Fourcroy et al, 2014).…”
mentioning
confidence: 99%